The (in)elasticity of moral ignorance - Marta Serra-Garcia; Nora Szech (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2019)
Ignorance enables individuals to act immorally. This is well known in policy circles, where there is keen interest in lowering moral ignorance. In this paper, we demonstrate the relevance of demand elasticity to ignorance by showing that small monetary incentives can significantly reduce ignorance. We contrast monetary incentives with social norms, which have little impact on ignorance and actually increase ignorance in less moral individuals. Using a longitudinal design, we document that ignorance is persistent across moral contexts and through time. We propose and structurally estimate a simple behavioral model in line with our findings.
Keywords: D83; D91; C91; 330; information avoidance; morality; unethical behavior; social norms